2018
DOI: 10.1155/2018/7987691
|View full text |Cite
|
Sign up to set email alerts
|

A Hierarchical Neural-Network-Based Document Representation Approach for Text Classification

Abstract: Document representation is widely used in practical application, for example, sentiment classification, text retrieval, and text classification. Previous work is mainly based on the statistics and the neural networks, which suffer from data sparsity and model interpretability, respectively. In this paper, we propose a general framework for document representation with a hierarchical architecture. In particular, we incorporate the hierarchical architecture into three traditional neural-network models for docume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…The new model has been tested against the original Doc2Vec and several other methods on some standard classification and sentiment analysis tasks. Other approaches in [76,77,78] have also proposed novel ANN-based structures to project document text into a lower dimensional vector.…”
Section: Background Information Chapter 2 Literature Reviewmentioning
confidence: 99%
“…The new model has been tested against the original Doc2Vec and several other methods on some standard classification and sentiment analysis tasks. Other approaches in [76,77,78] have also proposed novel ANN-based structures to project document text into a lower dimensional vector.…”
Section: Background Information Chapter 2 Literature Reviewmentioning
confidence: 99%
“…prediction-based or count-based methods-to real-valued vectors along with the context in which they are used [42]. Multiple variations of this structure exist [29,34,36,37,64]. This approach has been used for example in [39] to rank and explain influential aspects of law, or by [44] to predict the most relevant sources of law for any given piece of text using "neural networks and deep learning algorithms".…”
Section: Need For Massive Accesses (Legal Technologies)mentioning
confidence: 99%
“…Chandrasekaran because of their superior classification ability [21]. The authors of the paper "A Hierarchical Neural-Network Based Document Representation Approach for Text Classification" [22] integrate hierarchical neural architecture into traditional neural network methods and showed that their proposals outperform the corresponding neural network models for document classification. Nurulhuda and Ali [23] have mentioned three different weighting schemes to generate the word vectors which are Term Frequency-Inverse Document Frequency Binary Occurrence and Term Occurrence.…”
Section: Related Workmentioning
confidence: 99%